2020
DOI: 10.3390/agriculture10100469
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Soil Quality on Rainfed Wheat Yield

Abstract: Soil quality assessment based on crop yields and identification of key indicators of it can be used for better management of agricultural production. In the current research, the weighted additive soil quality index (SQIw), factor analysis (FA), and multiple linear regression (MLR) are used to assess the soil quality of rainfed winter wheat fields with two soil orders on 53.20 km2 of agricultural land in western Iran. A total of 18 soil quality indicators were determined for 100 soil samples (0–20 cm depth) fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The lack of a direct correlation in a specific study may be influenced by the specific conditions and the timing of data collection. Similarly, ( Nabiollahi et al., 2020 ) observed that the lack of significant correlations for some soil properties (CCE, pH, Silt, and EC) with the measured WY may not directly impact the WY in their study area.…”
Section: Discussionmentioning
confidence: 93%
“…The lack of a direct correlation in a specific study may be influenced by the specific conditions and the timing of data collection. Similarly, ( Nabiollahi et al., 2020 ) observed that the lack of significant correlations for some soil properties (CCE, pH, Silt, and EC) with the measured WY may not directly impact the WY in their study area.…”
Section: Discussionmentioning
confidence: 93%
“…Silt ranges from 4.00 to 61.30% with a mean value of 20.10 and CV 56.26%, from 0.50 to 54.50% with a mean value of 15.00 and CV 94.93% and from 0.20 to 54.00% with a mean value of 17.06 and CV 72.09%% in high, medium and low productivity zones respectively. Soil texture is a permanent physical property of soil that influences many functions of soil like nutrient and water uptake [13]. Variations in the soil texture might be due to the difference in nature and composition of the parent material.…”
Section: Texturementioning
confidence: 99%
“…There is an inseparable relationship between SQ and crop production (Bünemann et al, 2018). A preceding investigation underscored a remarkable 270% increase in crop yields when associated with robust SQ, in contrast to those linked with poorer SQ (Nabiollahi et al, 2020). Furthermore, the enhancement of SQ through the application of both organic and inorganic fertilizers has been validated as a means to secure sustainable crop yields (Ren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%